Megachurches and social engagement : public theology in practice - Cartledge, Mark J., 1962- (Global Pentecostal and Charismatic Studies, 2019)
This book is the first detailed academic study of megachurches in the UK. In particular, it explores the nature and significance of social engagement by megachurches in the context of London. The research contains empirical case studies of two Anglican and three African diaspora Pentecostal churches. As well as exploring the range of social engagement activities provided by these churches, the study offers explanations in term of theological motivations and the influence of globalisation. Subsequently, the book outlines the importance of the findings for the relationship between church and society in the contemporary context, addressing the implications for social policy and practice. The book advances discussions in public theology, megachurch studies, Pentecostal and Charismatic studies and ecclesiology.